Projected Effects of Disruptions to Human Immunodeficiency Virus (HIV) Prevention Services During the Coronavirus Disease 2019 Pandemic Among Black/African American Men Who Have Sex With Men in an Ending the HIV Epidemic Priority Jurisdiction. (6th June 2022) - Labs, Jennifer; Nunn, Amy S; Chan, Philip A; Bessey, S; Park, Carolyn J; Marshall, Brandon D L; Patel, Rupa R; Mena, Leandro A; Goedel, William C
Abstract: Background: Disruptions in access to in-person human immunodeficiency virus (HIV) preventive care during the coronavirus disease 2019 (COVID-19) pandemic may have a negative impact on our progress towards the Ending the HIV Epidemic goals in the United States. Methods: We used an agent-based model to simulate HIV transmission among Black/African American men who have sex with men in Mississippi over 5 years to estimate how different reductions in access affected the number of undiagnosed HIV cases, new pre-exposure prophylaxis (PrEP) starts, and HIV incidence. Results: We found that each additional 25% decrease in HIV testing and PrEP initiation was associated with decrease of 20% in the number of cases diagnosed and 23% in the number of new PrEP starts, leading to a 15% increase in HIV incidence from 2020 to 2022. Conclusions: Unmet need for HIV testing and PrEP prescriptions during the COVID-19 pandemic may temporarily increase HIV incidence in the years immediately after the disruption period.